Intelligible Violence: Media Scripts, Hindu/Muslim Women, and the Battle for Citizenship in Kerala - Usha Zacharias (Cultural Dynamics 2004; 16; 169, 2004)
This article analyzes media narrations of an incident of Hindu/Muslim communal conflict in Kerala, India. Depicting women as victims and agents of communal violence, the Media cast them in narratives of violation and retribution that are part of readymade Scripts of `communities at war'. Regional and communal conflict becomes intelligible through the tropes of gender difference, that of `Hindu wound', `Islamic terrorism', and `violated womanhood'. The narration of violence does not precede or follow gender politics. Rather, scripts of violence become intelligible through the logic of gender relations, as they strategically shift Hindu and Muslim political citizenship. The Ideologies that thread together gender, violence, and community, this article argues, critically underwrite the battle for political citizenship.